2021
DOI: 10.1007/s12015-021-10138-6
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity Communicates Using the Language of Extracellular Microvesicles

Abstract: The innate immunity system and extracellular microvesicles (ExMVs) both emerged early in the evolution of life, which is why its innate immunity cellular arm and its soluble-component arm learned, understood, and adapted to the “language” of ExMVs. This was most likely the first language of cell–cell communication during evolution, which existed before more specific intercellular crosstalk involving specific ligands and receptors emerged. ExMVs are involved in several processes in the body, including immune an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…This study focused on research that demonstrated a potential relationship of EV secretion induced by NMs. EVs are now recognized as an important pathway for intercellular communication by exchanging various types of payloads between cells [ 21 ]. While the cellular transfer of NMs and their payloads has received increasing attention, the role of EVs in this process remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study focused on research that demonstrated a potential relationship of EV secretion induced by NMs. EVs are now recognized as an important pathway for intercellular communication by exchanging various types of payloads between cells [ 21 ]. While the cellular transfer of NMs and their payloads has received increasing attention, the role of EVs in this process remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition or stimulation of EV secretion in response to external stimuli can cause alterations in cell communication and result in substantial implications to cell/tissue dysfunction and ultimately pathological consequences [ 14 , 17 , 19 ]. Emerging evidence suggests that the NM exposure of cells and organs stimulates the secretion and disturbs EV biogenesis by activating various biological processes that include immune-system activation, toxicity reduction mediated by exocytosis of NMs through EVs, and the induction of pro-thrombotic effects in cardiovascular and metabolic diseases [ 20 , 21 , 22 , 23 , 24 , 25 ]. Interestingly, EVs have demonstrated the importance of explaining the possible outcomes of many physiological processes, including the cytotoxic and inflammatory processes induced by NMs [ 10 , 20 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The density of urinary EV of DN patients were siginificantly reduced compared with T1DM ( 13 ). However, EV secretion mechanisms remove harmful substance from the plasma membrane, ensuring intracellular environmental balance ( 52 ). The substant reduces EV release, and crosstalk between cells about biogenesis and autophagy contributes to maintaining cellular homeostasis under external and internal stresses, leading to chronic kidney disease dysfunction ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…EV regulate the gene expression and signaling pathways of target cells by participating in antigen presentation, transmission of antigenic peptides or immunomodulatory molecules, and regulate adaptive immune response and innate immune response ( 6 ). The membrane attack complex C5b-C9 can be removed from the plasma membrane by exosome secretion and excretion mechanisms, ensuring cell survival and recovery from a large number of complement attacks ( 52 ). Besides that, the C1q protein binds to the surface of the EV by electrostatic action, and further to the combined with immunoglobulin, triggering the classical pathway of complement cascade activation and triggering the deposition of C3 and C4.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cell derived exosomes promote formation of metastases by initiating epithelial-mesenchymal-transition (EMT) within the tumor microenvironment. They will also travel to distant places (even passing the blood brain barrier) via various interstitial fluids in the extracellular space and be selectively taken up and induce transformation of normal cells into malignant cells [40][41][42][43][44].…”
Section: Exosomes and Malignant Cell Proliferationmentioning
confidence: 99%